An Analysis of Interaction Effects of China–South Korea and China– Australia FTAs and the Expanding TPP - Yuhong, Sun; Yifei, Mu; Yang, Jun (Naše gospodarstvo/Our economy, 2016)
On 5 October 2015, the Trans-Pacific Partnership Agreement (TPP) led by the U.S. was signed. Already, 12 countries1 have joined the agreement, but China has not. Thus, lots of research has focused on the negative effect of the TPP on China’s foreign trade. On the other hand, China is moving forward in its own efforts to establish bilateral free trade agreements (FTAs) and free trade zones. In June 2015, China–South Korea and China–Australia signed bilateral FTAs which went into effect in December 2015. Several questions were raised: Since South Korea and Australia are the major trade partners in the Pacific area and the bilateral FTAs will be effective before the TPP, will these FTAs’ positive effects on China’s foreign trade offset some of the negative effects of the TPP? If China and the U.S. adopted a competitive trade policy, which countries would benefit? If China and the U.S. adopted a cooperative trade policy, how would the trade value and economic welfare change? This paper simulates and analyses the mutual effects of China–South Korea and China–Australia FTAs and the enlarging TPP using the computable general equilibrium model. The major conclusions drawn suggest that China–South Korea and China–Australia FTAs will significantly offset the TPP’s negative effect on China’s foreign trade. If China is not included, the U.S. economic benefit from the TPP will be limited. The economic welfare for a country like Australia, which joined both the bilateral FTA and the TPP, will be increased the most. In the long run, China joining the TPP would be the most beneficial decision for its national interest. However, if the TPP cannot be approved by the US congress, the U.S.’s economic indicators and export would be decreasing sharply. China’s economy and export will benefit from FTAs.